The Role of Body Language in Islamic Public Speaking to Influence Audiences in the Digital Era - Waliulu, Habiba; Sok, Vann; Rith, Vicheka (Journal International Dakwah and Communication, 2025)
The digital era has significantly transformed public speaking, especially in Islamic discourse, where the influence of body language plays a crucial role in engaging and persuading audiences. Body language, encompassing gestures, facial expressions, posture, and eye contact, can enhance the effectiveness of spoken words and create a stronger connection between the speaker and the audience. This research explores the role of body language in Islamic public speaking, focusing on its impact on influencing audiences within the context of digital platforms such as webinars, podcasts, and live-streamed sermons. Using a qualitative research design, this study analyzes interviews with experienced Islamic speakers, audience feedback, and case studies of prominent Islamic public speaking events conducted in digital spaces. The findings reveal that effective body language significantly improves audience engagement, comprehension, and emotional connection, even in virtual settings. Speakers who utilized expressive gestures and appropriate posture were more successful in delivering their messages and retaining the audience’s attention. The study concludes that body language remains a key tool for enhancing Islamic public speaking, even in the digital age, where it contributes to the effectiveness of communication and strengthens the delivery of religious messages. These findings offer insights into improving the quality of Islamic discourse on digital platforms.